2004
DOI: 10.1081/ja-120027764
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Other Factors Associated with the Nonmedical Use of Abusable Prescription Drugs

Abstract: Although there is extensive research on gender differences in the use of alcohol and illicit substances, few studies have examined gender differences in nonmedical prescription drug use, Using data from the 1991 National Household Survey on Drug Abuse (NHSDA), based on a sample of 3185 persons, logistic regression analysis is employed to determine how gender and other factors affect the likelihood of past-year nonmedical prescription drug use. Analysis revealed that women are significantly more likely than men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
157
5
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(185 citation statements)
references
References 26 publications
17
157
5
6
Order By: Relevance
“…One previous study concerning non-medical use of sedatives and tranquilizers showed that female gender was associated with non-medical tranquilizer but not sedative use (Simoni-Wastila et al, 2004). Our analysis does not differentiate between the two sub-types of medication.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…One previous study concerning non-medical use of sedatives and tranquilizers showed that female gender was associated with non-medical tranquilizer but not sedative use (Simoni-Wastila et al, 2004). Our analysis does not differentiate between the two sub-types of medication.…”
Section: Discussioncontrasting
confidence: 64%
“…Our findings should be cautiously compared to other studies (Conway et al, 2006;Goodwin and Hasin, 2002;Simoni-Wastila et al, 2004) given our exclusion of 12-18 year olds, the larger sample size we have employed and our focus on past-year rather than lifetime prevalence of substance use and psychiatric characteristics. One previous study concerning non-medical use of sedatives and tranquilizers showed that female gender was associated with non-medical tranquilizer but not sedative use (Simoni-Wastila et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Esse achado sugere um padrão de medicalização semelhante ao observado em mulheres adultas, que buscam alívio para seus problemas domésticos ou laborais através de "calmantes químicos". Essa associação entre gênero e consumo de medicamentos tem sido analisada em estudos direcionados para a população adulta, mas não para crianças e adolescentes 12,13 .…”
Section: Discussionunclassified
“…Despite the increasing concern about the recent rise in the extramedical use of opioid analgesics, only a few studies have investigated problems associated with their use (e.g., dependence symptoms) (Huang et al, 2006;Martins et al, 2007;Simoni-Wastila et al, 2004). Many of the concerns about the current "epidemic" and its associated problems are founded largely on anecdotal and clinical reports Zacny et al, 2003).…”
Section: Introductionmentioning
confidence: 99%